2017
DOI: 10.12659/msm.900084
|View full text |Cite
|
Sign up to set email alerts
|

miR-200bc/429 Inhibits Osteosarcoma Cell Proliferation and Invasion by Targeting PMP22

Abstract: BackgroundMicroRNAs (miRNAs) are small non-coding RNAs which play a crucial role in diverse biological processes and could contribute to cancer development and progression. MiR-200bc/429 have been found to be aberrantly expressed in osteosarcoma (OS). However, the features of miR-200bc/429 in the tumorigenesis and progress of OS remain poorly understood.Material/MethodsThe miR-200bc/429 expression was firstly identified in human OS clinical samples and cell lines by quantitative real-time PCR (qRT-PCR). After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Osteosarcoma is one of the most prevalent types of bone tumors, mainly detected in adolescents and children. It has been reported that around 70% of osteosarcoma patients are ages 10–25 years [ 1 ]. The development of chemoresistance among osteosarcoma patients forms a bottleneck in the treatment of osteosarcoma [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Osteosarcoma is one of the most prevalent types of bone tumors, mainly detected in adolescents and children. It has been reported that around 70% of osteosarcoma patients are ages 10–25 years [ 1 ]. The development of chemoresistance among osteosarcoma patients forms a bottleneck in the treatment of osteosarcoma [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…OS typically presents between the ages of 10 and 20 years or in elderly patients (2,3) and generally develops from primitive mesenchymal bone-forming cells in the long bones (4). At present, the therapeutic options for OS are surgery and intensive multi-agent chemotherapy, including cisplatin, doxorubicin, ifosfamide and methotrexate (5). The 5-year survival rate of patients with OS without metastases is 60-70%, depending on the use of chemotherapy (6).…”
Section: Introductionmentioning
confidence: 99%
“…The PMP22 protein regulates cell growth cycle, cell adhesion, and apoptosis, and is irregularly expressed in various malignant tumors. Its overexpression is associated with the occurrence and progression of lung cancer, breast cancer, gastric cancer, pancreatic cancer, and osteosarcoma [ 39 , 40 ]. Hence, PMP22 might have a great value in the clinical treatment and prognosis of malignant tumors.…”
Section: Biological Functions Of the Pmp22 Protein Familymentioning
confidence: 99%